Realization utility with adaptive reference points. (31st July 2018) - He, Xuedong; Yang, Linan
Abstract: Experimental studies have demonstrated that a typical investor derives utility of the gain and loss, relative to certain reference point, realized at each sale of a stock, and that the reference point adapts asymmetrically to the stock's prior gains and losses in that the adaptation to a gain is more substantial than to a comparable loss. This empirical finding motivates us to consider a dynamic trading problem in which an agent decides when to sequentially sell and buy a stock in order to maximize her utility of terminal wealth and realized gains and losses based on a reference point that adapts asymmetrically to the stock's prior gains and losses. We show that this agent is more reluctant to sell the stock at a loss than another agent whose reference point does not adapt to the stock gain or loss at all, leading to a higher percentage of gains realized (PGR) and a lower percentage of losses realized (PLR). We also show that when the agent weighs the utility of realized gains and losses more heavily in her investment criteria, she trades the stock more frequently, the PGR becomes lower, and the PLR becomes higher.